Giant Molluscum Contagiosum - Thappa Devinder Mohan; Karthikeyan Kaliaperumal; Manjunath J.V (Wolters Kluwer Medknow Publications, 2002)
A case of giant molluscum contagiosum (GMC) with AIDS is described here. Such GMC lesions usually occur in the late stages of HIV disease and are considered to be a marker of AIDS.